Health Policies, Health Politics : The British and American Experience, 1911-1965 - DANIEL M. FOX (Princeton University Press, 2014)
MANY of the vexing problems of health affairs in Britain and the United States in the 1980s are the unanticipated consequences of a policy, more precisely, a set of policies and ideals that, for most of this century, seemed self-evidently the best way to advance science and improve the health of the public. I call this policy hierarchical regionalism, by which I mean a particular logic of organization based upon a theory of how medical knowledge is discovered and disseminated. I use the phrase hierarchical regionalism to summarize three assumptions that became the basis of health policy in Britain, the United States and, I believe, most industrial countries in the twentieth century. These assumptions are: 1) The causes of cures for most diseases are usually discovered in the laboratories of teaching hospitals and medical schools. 2) These discoveries are then disseminated down hierarchies of investigators, institutions, and practitioners that serve particular geographic areas. 3) Health policy should stimulate the creation of hierarchies in regions that lack them and make existing ones operate more efficiently